Faith-based marketing : the guide to reaching 140 million Christian consumers - Stielstra, Greg.; Hutchins, Bob. (Hoboken, N.J. : Wiley, 2009)
"Faith-Based Marketing provides everything you need to understand the Christian consumer power niche and effectively reach it. It explains who makes up that community, what they want, and what it takes to appeal to them. Then, based on survey research from believers across the country and interviews with experts, it provides practical guidance for creating faith-based marketing plans that work."--Jacket
Meet the Christian Consumer. The Overlooked 140 Million Person Market -- Lose Your Faith Everything You Think You Know About Christians Is Wrong -- Meet The Real Christian Consumer They Are No Different. They Are So Different. -- Darned If You Do, Darned If You Don't Common Mistakes Marketers Make -- How to Market to Christians. Meet and Greet How to Get to Know your Audience -- Serve, Do n't Sell Building Your Brand -- Word-of-Mouth -- Radio Strategies -- Print Strategies -- Online Strategies -- Direct Marketing To Christians -- Reaching Pastors What Works and What Doesn't Work -- How to Market Your Church -- Key Resources for Christian Marketers.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Marketing; Selling; Marketing; Vente; marketing; selling; BUSINESS & ECONOMICS -- Marketing -- General; BUSINESS & ECONOMICS -- Distribution; Marketing; Selling